The associated matrix are used to calculate the vibrations of continuous plates - Raspopov, A. S. (Science and Transport Progress, 2010)
The associated matrices are obtained and the technique of their application for calculation of continuous plate vibration with continuous distribution of mass and various boundary conditions is developed. The solutions for free vibrations of orthotropic plate taking into account the rotation inertia, shears and longitudinal forces are also presented.